Optimizing Performance and Profit for Better Sustainability: A Review on Protease Application in Aqua Feed - Kabir Chowdhury, M A (Avances en Nutrición Acuicola, 2015)
Optimizing utilization of nutrients in aqua feeds by supplementing various dietary enzymes have recently been considered by nutritionists and formulators worldwide to combat fluctuating price, availability and quality of commonly used plant and animal proteins. Biological factors such as growing stage, age, species types, environmental factors such as temperature, pH and dissolved oxygen, and feed composition appeared to significantly affect endogenous enzyme production. A better understanding of these effects on digestive proteases will allow optimizing the use of supplementary enzymes, and in turn, will assist in better utilization of dietary nutrients. The main objective of using dietary protease has been to compensate digestive enzymes to promote growth and efficiency of nutrient utilization and reduce nutrient excretion. Little focus has been paid to assessing their effects on improving digestibility of raw materials or feed quality or gut health and specific immune response. This review mainly digestive proteases, their interactions with various ingredients or diet composition in different fed species, use of dietary proteases and its implications on the industry in optimizing performance and profit.